INTERACTION OF PRIMARY DICTIONARY AND CONTEXTUALLY IMPOSED MEANING - Ruziev Khusniddin Bakhritdinovich (Лучшие интеллектуальные исследования, 2024)
Abstract: This article deal with interaction of primary dictionary and contextually imposed meaning Different kind of words in English are explained and analyzed.